Impact Assessment of Demographic Factors on Investment Objectives of Women (International Journal of Scientific Research in Science and Technology, 2025)
This study seeks to investigate the primary investing objectives of women and assess the influence of demographic factors on their financial objectives. The study employs primary data and utilizes Exploratory Factor Analysis (EFA) to classify investment objectives into meaningful factors. Furthermore, One-Way ANOVA is utilized to evaluate the impact of demographic characteristics, including age, education, income, marital status, occupation, and family structure, on investment objectives. The data indicate two principal investment objectives among women: wealth-building investments, which prioritize capital appreciation and long-term financial growth, and security-oriented investments, which emphasize financial safety, retirement savings, and family welfare. Findings demonstrate that marital status, income level, and the number of dependents substantially affect security-oriented investing decisions, while family responsibilities shape wealth accumulation objective. The study's findings enhance the discourse on gender-specific investment behavior and offer significant implications for policymakers, financial institutions, and educators to develop customized financial literacy programs and investment products that adequately meet the distinct needs of women investors.
Keywords: Investment Objectives; Investment Decision Making; Women Investors; Demographic Factors; Financial Security